Accuracy of Antibiotic use in Pediatric ISPA Patients at Hospital X Malang City - Larasati, Debby Ayu; Permata, Agung; Herlila Sekti, Beta (Riviera Publishing, 2024)
Acute Respiratory Tract Infections (ARI) are one of the most serious health problems in the world. According to UNICEF and WHO, ISPA is one of the leading causes of death in humans compared to the number of deaths from AIDS, malaria and measles. The prevalence period of ISPA, which is calculated within two years, according to the diagnosis by health workers in 2018, is known to reach 1,017,290, of which as many as 182,338 cases occur in children aged 12 years and under. Acute Respiratory Tract Infection (ARI) generally occurs in children and adults and is the main cause of mild morbidity. This study aims to determine the rationale for the use of antibiotics in pediatric patients with upper respiratory tract infections at Hospital X Malang City with parameters that include the right patient, the right indication, the right dose, and the right duration. This type of research is a type of non-experimental research with a descriptive research design and retrospective data collection. The results of the demographic data obtained were more male patients, namely 37 patients (52.8%), the highest age range of 1-5 years (50%), the most common diagnosis, namely pharyngitis (58.6%), and the suitability of the use of antibiotics in pediatric ARIA patients at Hospital X Malang City was in accordance with the guidelines of Pharmaceutical Care for respiratory diseases in 2005. and 100% right doe, and 100% right duration.